Long-term effects of weed management on earthworm abundance in a banana plantation in Davao City, Southern Mindanao, Philippines - Rasco, Eufemio T. Jr.; Oguis, Georgianna Kae R.; Fusilero, Ma. Abegail T.; Taya, Hanna Mia Monica C.; Lacsamana, Michael G.; Ragas, Richie Eve G. (2011)
Earthworm densities have been regarded as reliable indicators of soil health. A long-term field experiment was conducted in two sites (15% and 25% slope) to compare the effects of manual and chemical weeding (using paraquat and glyphosate) and determine other factors that may affect earthworm populations in a banana plantation. Based on four years of field observation, no significant difference in earthworm count between manual and chemical plots (15% slope: F-ratio: 0.96, p = 0.43; 25% slope: F-ratio: 14.18, p =0.06) were observed. The earthworm species composition was found to differ between the two sites. The 15% site tends to have a higher earthworm population compared to the 25%-slope site, likely because of the former's higher soil organic matter content. Earthworm populations were on a declining trend in both treatments for both sites, but regression analyses show these trends to be insignificant. Rainfall, organic mulch, and weed cover were not significantly correlated with the earthworm counts. However, the declining pH in both sites could help explain the decline in earthworm populations. Pontocolex corethrurus showed significant avoidance response to normal glyphosate concentrations (8.055 x 10-3 mL per 350 g soil) (p = 0.03), but not to paraquat (1.5 x 10-3 g per 350 g soil) (p =0.55). Experiments suggest that both weed management treatments do not pose a significant threat to earthworms under the conditions studied. The negative effect of declining pH needs further study.
Keywords: Weed management; Earthworms; Banana plantations--Davao City--Philippines